Secrets of the hair follicle: now on your iPhone - Millar, Sarah E. (Dev Cell, 2015)
Skin development requires communication between epithelial and mesenchymal cells, melanocytes and neurons. Sennett et al. (2015) shed new light on these mechanisms by simultaneously profiling multiple different cell types in embryonic mouse skin at the onset of hair follicle formation.